Analysis of Learning Implementation, Self Efficacy, and Students Attitude Towards Science in Relation with Science Literacy (Journal of Innovative Science Education, 2020)
Student science literacy is influenced by external and internal factors. One external factor is learning implementation, while internal factors are self efficacy and attitude towards science. This study aims to analyze the science literacy of students, the linkages of learning implementation, self efficacy, and attitudes toward science in a linear and simultaneous ways. This study uses explanatory research design at SMAN 1 Cepiring and SMAN 1 Kaliwungu. The subjects of this research are 125 students. Data collection techniques through observation, questionnaire, psychological scale, and tests. Data analysis used descriptive statistics, proportion test, one sample T test, correlation and regression. The results showed science literacy of students in the medium category, achieving a minimum average completeness and classical completeness of 75%. The linkages of the learning implementation with science literacy was 10,7%, self efficacy was 11,7% and attitudes toward science was 9,5%. The linkages of learning implementation, self efficacy, and attitudes toward science with science literacy simultaneous ways shows that there is a positive and significant relationship in the low category with a coefficient of determination of 18,7%. Result shows that collaboration between external and internal factors have shown a higher relationship in influencing students' science literacy.